1989
DOI: 10.1128/aem.55.6.1426-1434.1989
|View full text |Cite
|
Sign up to set email alerts
|

Expression by Soil Bacteria of Nodulation Genes from Rhizobium leguminosarum biovar trifolii

Abstract: Gram-negative, rod-shaped bacteria from the soil of white clover-ryegrass pastures were screened for their ability to nodulate white clover (Trifolium repens) cultivar Grasslands Huia and for DNA homology with genomic DNA from Rhizobium leguminosarum biovar trifolii ICMP2668 (NZP582). Of these strains, 3.2% were able to hybridize with strain ICMP2668 and nodulate white clover and approximately 19% hybridized but were unable to nodulate. Strains which nodulated but did not hybridize with strain ICMP2668 were no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Several reports in which nonsymbiotic R. leguminosurum were qualitatively recovered directly from soils (Jarvis et al 1989; Soberon-Chavez h Najera 1989; Segovia et al 1991;Laguerre et af. 1993) have indicated that these bacteria may constitute a substantial fraction of field populations.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports in which nonsymbiotic R. leguminosurum were qualitatively recovered directly from soils (Jarvis et al 1989; Soberon-Chavez h Najera 1989; Segovia et al 1991;Laguerre et af. 1993) have indicated that these bacteria may constitute a substantial fraction of field populations.…”
Section: Discussionmentioning
confidence: 99%
“…In the pioneering studies of Bohlool and Schmidt (4), an indigenous soil-borne actinomycete was found to cross-react strongly with a fluorescent antibody to B. japonicum. More recently, nonnodulating bacteria that were either antigenically related or that showed partial DNA homology to symbiotically competent biovars of R. leguminosarum have been recovered directly from soil (21,43). Although the antiserum to serotype 36 of R. leguminosarum bv.…”
Section: Discussionmentioning
confidence: 99%
“…All but one of the S. meliloti isolates from soil carried megaplasmids and all of them were able to nodulate and fix nitrogen in symbiosis with alfalfa, thus only symbiotic S. meliloti were isolated from soil. This result contrasts with the relatively large numbers of non‐symbiotic R. leguminosarum isolated from soils [14–17]. This may indicate that genes essential for the survival of S. meliloti in soils are located on the very large Sym megaplasmid and thus linked to symbiotic genes.…”
Section: Discussionmentioning
confidence: 74%
“…Methods have recently been developed to isolate Rhizobium and Bradyrhizobium strains directly from soil [14–19]. Symbiotic and non‐symbiotic Rhizobium leguminosarum were isolated directly from soils containing indigenous populations of this bacterium [14–17]. To our knowledge, there is only one report of direct isolation of S. meliloti from soil [20].…”
Section: Introductionmentioning
confidence: 99%